A murder like no author : a Main Street book club mystery - Lillard, Amy (Main street book club mysteries, 2021)
"Bookstore owner Arlo and her Friday Night Book Club sleuths are going to have to read between the lines to solve this mystery! It's movie time in Sugar Springs and the whole town is pitching together to get the historical Coliseum Theater ready for the event of the year-the premiere of Missing Girl, local author Wally Harrison's bestselling novel turned film. Thrilled to bring tourists to Sugar Springs, the town comes together to host the late author's event. But when a stranger arrives, boasting he has definitive proof that Wally didn't write Missing Girl...well, drama leaps from the page into real life. Mishaps start taking place around the theater-and then the stranger is discovered dead in his hotel room right before his press conference. Can Arlo and her Friday night book club to sleuth out the killer and solve the mystery before the town's Hollywood dreams go up in smoke?"--